Is there a heat or eat trade-off in the UK? - Timothy K. M. Beatty; Laura Blow; Thomas F. Crossley (Institute for Fiscal Studies (IFS), 2011)
We merge detailed household level expenditure data from older households with historical local weather information. We then test for a heat or eat trade off: do houseolds cut back on food spending to finance the additional cost of keeping warm duing cold shocks? We find evidence that the poorest of older households are unable to smooth spending over the worst temperature shocks. Statistically significant reductions in food spending are observed in response to temperatures two or more standard deviations colder than expected (which occur about one winter month in forty) and reductions in food expenditure are considerably larger in poorer households.
Keywords: 330; Privater Haushalt; Altersgruppe; Ausgaben; Heizungsanlage; Nahrungsmittelkonsum; Großbritannien